ANALISIS TINGKAT KETAHANAN PANGAN RUMAH TANGGA PETANI BAWANG MERAH DI DESATUNGKU JAYA KECAMATAN SOSOH BUAY RAYAP KABUPATEN OGAN KOMERING ULU (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2018)
Analysis of Household Food Security Rate of Red Onion Farmers in Tungku Jaya Village, Sosoh Buay District Sub-district, Ogan Komering Ulu District. The purpose of this study is to analyze the level of food resilience of lowland garlic farmers in Tungku Jaya village, Sosoh Buay sub district, Ogan Komering Ulu district. This research has been conducted in Tungku Jaya Village, Sosoh Buay Termap Sub District, Ogan Komering Ulu District, where the determination of the area is done purposively. Implementation of this research conducted in January 2017 - July 2017. The data obtained is tabulated and described descriptively and qualitatively.The research method used in this research is survey method used to obtain field facts by using questionnaire as data collection tool. Sampling method used in this research is saturated sampling method where all data is taken all that is from 1 district in regency of ogan komering ulu. Based on the results of the research, the level of food resilience of onion farmer households in Tungku Jaya Village, Sosoh Buay Termap Sub-district of Ogan Komering Ulu District shows that food security with food security level 54,74% from total household expenditure, because the proportion of food expenditure is low (< 60 percent household expenditure) and consuming enough energy (> 80 percent of the energy adequacy requirement).